2018
DOI: 10.52981/jfst.vi5.359
|View full text |Cite
|
Sign up to set email alerts
|

The Efficiency of Two Nile Fishes as Biocontrol Agents Against Different Stages of Schistosomiasis Intermediate Host.

Abstract: The present investigation is dealing with the biological control of schistosome intermediate host, two Nile fishes Debs (Labeo niloticus) and the Nile Bulti or Tilabia (Cyrinus carbio) were selected to determine their efficiency to control schistosomiasis intermediate host (snails). Six laboratory sets of experiments were designed, three for Bulinus truncatus and other three for Biomphalaria pfeifferi. The first set in each snail species were control group, while the other two provided with the two Nile fishes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The earliest attempts at biological control of Biomphalaria were based on predation (Tables 1, 2, and 3), by fish (OLIVER- GONZÁLEZ, 1946). Laboratory studies have shown that Sarotherodon mossambica, Tilapia rendalli, T. nilotica, Gambusia affinis, Labeo niloticus, and Cyrinus carbio all prey on the egg masses and neonates of Biomphalaria (GRABER et al, 1981;ANDRADE, 1982;SULIEMAN et al, 2015;AFIFI & AHMED, 2018). Other species have been observed to prey on adult snails, and these include: Sargochromis codringtoni, G. affinis, L. niloticus, C. carbio, and Clarias gariepinus (CHIMBARI et al, 1996;1997;GASHAW et al, 2008;SULIEMAN et al, 2015;AFIFI & AHMED, 2018).…”
Section: Predatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The earliest attempts at biological control of Biomphalaria were based on predation (Tables 1, 2, and 3), by fish (OLIVER- GONZÁLEZ, 1946). Laboratory studies have shown that Sarotherodon mossambica, Tilapia rendalli, T. nilotica, Gambusia affinis, Labeo niloticus, and Cyrinus carbio all prey on the egg masses and neonates of Biomphalaria (GRABER et al, 1981;ANDRADE, 1982;SULIEMAN et al, 2015;AFIFI & AHMED, 2018). Other species have been observed to prey on adult snails, and these include: Sargochromis codringtoni, G. affinis, L. niloticus, C. carbio, and Clarias gariepinus (CHIMBARI et al, 1996;1997;GASHAW et al, 2008;SULIEMAN et al, 2015;AFIFI & AHMED, 2018).…”
Section: Predatorsmentioning
confidence: 99%
“…Laboratory studies have shown that Sarotherodon mossambica, Tilapia rendalli, T. nilotica, Gambusia affinis, Labeo niloticus, and Cyrinus carbio all prey on the egg masses and neonates of Biomphalaria (GRABER et al, 1981;ANDRADE, 1982;SULIEMAN et al, 2015;AFIFI & AHMED, 2018). Other species have been observed to prey on adult snails, and these include: Sargochromis codringtoni, G. affinis, L. niloticus, C. carbio, and Clarias gariepinus (CHIMBARI et al, 1996;1997;GASHAW et al, 2008;SULIEMAN et al, 2015;AFIFI & AHMED, 2018). In the field, Serranochromis macrocephala and Astatoreochromis alluadi were able to reduce Biomphalaria populations (DE BONT & DE BONT, 1952;MCMAHON et al, 1977).…”
Section: Predatorsmentioning
confidence: 99%